The effectiveness of used plastic bottles as media in the biofilter for reducing BOD5 and COD in laundry waste - Ranggi Efendi; M.Hasbi M.Hasbi; Eko Purwanto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractUsed plastic bottles can be used for biofilter media, as microorganisms may attach in the bottle surface. To understand the effectiveness of the number of plastic bottles in the anaerob tank in reducing BOD5 and COD in laundry waste, a research has been done in October-December 2019. There were 3 treatments applied, namely P1 (25 bottles,  11.540 cm2 surface area),  P2 (50 bottles, 23.080 cm2 surface area) and  P3 (75 bottles,  34.619 cm2  surface area), with 3 replications in each treatments. The seeding time of the biofilm was 25 days and the retention time of the water was 12 hours. The effectiveness of BOD5 decrement was 48.4%, 61.1% dan 69.4% in P1, P2, and P3 respectively. While the effectiveness of COD decrement was 44.5%, 50% and61.8% in P1, P2, and P3 respectively. Based on data obtained, it can be concluded that the biofilter that was completed with plastic bottleswas able to reduce the BOD5 and COD in the laundry liquid waste and P3 provided the best result.Keywords: anaerob, bacteri, waste management, plastic bottle re-use